Exogenous murine antimicrobial peptide CRAMP significantly exacerbates Ovalbumin-induced airway inflammation but ameliorates oxazolone-induced intestinal colitis in BALB/c mice. Issue 1 (2nd January 2018) - Li, Yang; Chu, Xiaojie; Liu, Cunbao; Huang, Weiwei; Yao, Yufeng; Xia, Ye; Sun, Pengyan; Long, Qiong; Feng, Xuejun; Li, Kui; Yang, Xu; Bai, Hongmei; et al.
ABSTRACT: Cathelicidin has been reported to be multifunctional. The current study aimed to investigate the influences of exogenous cathelicidin-related antimicrobial peptide (CRAMP) on inflammatory responses in different disease models. In OVA-induced allergic airway inflammation, CRAMP significantly enhanced the infiltration of inflammatory cells and accumulation of proinflammatory Th2 cytokine IL-13 and IL-33 in bronchial alveolar lavage fluid (BALF), exacerbated lung tissue inflammation and airway goblet cell hyperplasia, and elevated OVA-specific IgE level in serum. In oxazolone-induced intestinal colitis, the expression levels of CRAMP and its receptor FPR2 significantly increased in comparison with those of TNBS-induced mice, vesicle and normal controls. Exogenous CRAMP significantly prevented the development of ulcerative colitis, evidenced by improved body weight regain, decreased colons weight/length ratio, elevated epithelial integrity, and ameliorated colon tissue inflammation. In addition, pro-inflammatory cytokines TNF-α, IL-1β, IL-4 and IL-13, as well as chemokines CXCL2 and CXCL5 for neutrophils recruitment were significantly decreased in CRAMP-treated mice, and epithelial repair-related factors MUC2 and Claudin1 were increased, determined by real time-PCR and ELISAs. The results indicated that although CRAMP has pro-inflammatory effects in airway, local application of exogenous CRAMP might be a potential approach for the treatment of ulcerative colitis.